2015
DOI: 10.1038/srep12158
|View full text |Cite
|
Sign up to set email alerts
|

Design and improvement of artificial redox modules by molecular fusion of flavodoxin and flavodoxin reductase from Escherichia coli

Abstract: A variety of fusion proteins between the versatile redox partners flavodoxin (FldA) and flavodoxin reductase (Fpr) from Escherichia coli was constructed with the aim to improve the electron transfer properties. The order in which FldA and Fpr were fused and the linker region between them was varied in a systematic manner. A simple molecular tool, designated “DuaLinX”, was developed that facilitated the parallel introduction of flexible glycine-rich and rigid proline-rich linkers between the fusion partners in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Insertion of a suitable linker between the fusion partners however, substantially improved the overall performance. Herein, long ([E/L]PPPP) n linkers (n = 4–5) were particularly effective (Figs 1 and 4 ), which is consistent with previous findings for fusions between E. coli FldA and Fpr 19 . At protein concentrations ≥4 µM, the superior construct YR-P5 acted as a nearly equivalent substitute for non-fused Fpr/YkuN in driving CYP109B1 catalysis (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Insertion of a suitable linker between the fusion partners however, substantially improved the overall performance. Herein, long ([E/L]PPPP) n linkers (n = 4–5) were particularly effective (Figs 1 and 4 ), which is consistent with previous findings for fusions between E. coli FldA and Fpr 19 . At protein concentrations ≥4 µM, the superior construct YR-P5 acted as a nearly equivalent substitute for non-fused Fpr/YkuN in driving CYP109B1 catalysis (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…YkuN was fused to the N-terminus of Fpr, leaving the C-terminus of Fpr free, as it was demonstrated previously that attachment of FldA to the C-terminus of Fpr leads to reduced enzyme function, whereas constructs with the fusion partners in reversed order were substantially more active 19 . Attachment of the flavodoxin to the C-terminus of Fpr likely interferes with the function of the aromatic residues at the extreme C-terminus of Fpr, which are important for NADPH binding and electron exchange 30 32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when we applied tethering strategies to increase the affinity of the Cytochrome P450 and the redox partners towards each other, we observed higher titers with the non-natural redox partners. Tethering strategies have previously been applied to several Cytochrome P450 enzymes, both in vitro [35,42,[48][49][50][51] and in vivo [42,48]. The in vitro studies showed that tethered redox complexes are able to overcome the need to use an excess of redox partners over the Cytochrome P450 enzyme, to compensate for low protein-protein affinities (typically a five-to 20-fold molar excess of ferredoxin is used in vitro).…”
Section: Discussionmentioning
confidence: 99%